Kompres Serai Hangat Mengurangi Nyeri Rheumatoid Arthritis - Dwi Kartika Pebrianti; Mila Triana Sari (Jurnal Abdimas Kesehatan (JAK), 2022)
Rheumatoid arthritis occurs in 0.5-1% of the adult population in developed countries. Based on data from Riskesdas (2018), there is an increase in joint disease, originally there was 7.3%, increased to 11.9%. The high incidence of Rheumatoid Arthritis is influenced by many factors, namely age, gender, genetics, sex hormones, and immunity. Rheumatoid arthritis should not be ignored, because it will damage the joints which cause severe pain. One of the measures that have been shown to be effective non-pharmacologically to reduce pain is to warm the affected joint. Warm compresses can be used in the treatment of pain and relax tense muscles. Plants that have substances as warming, anti-inflammatory and can increase blood flow such as lemongrass. The purpose of this activity is to provide education about rheumatoid arthritis and how to reduce pain by applying warm lemongrass compresses to residents in Lebak Bandung village. This service activity was carried out on 29-30 September 2020, by visiting the homes of residents who were the target of the activity. The target is the residents of Lebak Bandung village as many as 20 people. This activity consists of providing education with leaflet media and demonstrations using models. After education, all targets can understand and be able to demonstrate the application of warm lemongrass compresses. It is recommended that educational activities can be carried out routinely regarding health problems that are needed by the community